Highly Permeable, Electrically Switchable Filter for Multidimensional Sorting of Suspended Particles - Laura Weirauch; Jasper Giesler; Georg R. Pesch; Michael Baune; Jorg Thöming (Powders)
The creation of highly specific particle systems in the nano- and micrometer size range is a challenging task. The demand for particle systems with narrowly distributed properties is increasing in many applications, especially for use in high-tech products. Conventional separation techniques often reach their limits in the micrometer size range or become (labor-)intensive, which makes them economically or ecologically unsustainable. In addition, sorting based on several properties is rarely feasible in just one separator. Dielectrophoretic processes can be a viable option for complex sorting tasks like this, given their ability to address several particle properties and their high degree of selectivity. In this paper, we summarize the progress of a project in which the capability of dielectrophoretic methods for multidimensional sorting of microparticles was investigated. We were able to develop an operation mode for multidimensional sorting of microparticles using dielectrophoresis as well as a scalable electrically switchable filter. This creates a basis for high-throughput and multi-target sorting of technical microparticles using dielectrophoretic processes.